The Application Of The Discovery Learning Model To Improve Student Learning Outcomes In Class Xi Nkn A Smk Negeri 7 Palu - Fikar, Zul; Amus, Sunarto; Sunarto, Sunarto (Jambura Journal Civic Education, 2024)
This research focuses on problems related to student learning outcomes in class XI NKN A SMK Negeri 7 Palu academic year 2023/2024 even semester. This study aimed to improve student learning outcomes in Pancasila Education subjects by using the discovery learning model in class XI NKN A SMK Negeri 7 Palu. Classroom Action Research (PTK) is the type of research used in this study. Classroom Action Research (PTK) was carried out for two cycles. Each cycle consists of 2 meetings, which include: (1) planning action, (2) implementing action, (3) carrying out observations, and (4) reflecting. The results of this study showed that the achievement of learning outcomes increased from the initial conditions to cycle II. Each cycle consists of 2 meetings, including Planning, Action, and Observation and Reflection, where each cycle consists of 2 meetings. The achievement of learning outcomes has reached the specified success indicators, with the achievement of learning outcomes increasing from 72.61% in the previous cycle to 83.09% in cycle II. This increase shows the success of applying the Discovery Learning learning model so that it can be said to have improved learning outcomes in class XI NKN A SMK Negeri 7 Palu.